Bibliometric Analysis of Publication on Protein Nanoparticle Using VOSviewer - Riska Kurnelia Ananda; Asep Bayu Dani Nandiyanto (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: A Study to determine the development of research can be done by bibliometric analysis technique. There are many studies that have been carried out on bibliometric analysis. However, research on bibliometric analysis of published data in the field of protein nanoparticles that has been carried out specifically to determine research development has not been carried out. Objective: This study aims to examine the development of protein nanoparticle research through a bibliometric approach. Methods: The article data was obtained from the Google Scholar database using the publish or perish reference manager software. The keyword "Protein Nanoparticles" is used with a publication time span from 2012 to 2022. Data processing uses Microsoft Excel. Computational mapping using VOSviewer. Results: The article data obtained and considered relevant were 390 articles. The results of the analysis of the development of protein nanoparticle publications in the last 10 years show quite frequent fluctuations. Research fluctuations occurred in 2012 to 2020. There was a decline in 2020-2022 from 35 in 2020 to 19 in 2022. In 2012 and 2014 research on protein nanoparticles became popular, with 47 studies each. Conclusion: Based on the results of mapping the collected article data, it can be seen that the keyword protein nanoparticles is still rarely used in research. It can be concluded that the field of protein nanoparticles is still very likely to be researched and associated with other terms, this will have a higher impact on the novelty of the research.